Vegetational assessment, biomass, and carbon sink estimation of Sto. Niño Mangrove Stand Bontoc, Southern Leyte, Philippines - Kabilte, Vienneza Lou G.; Parilla, Richard B. (2023)
Mangroves' role in carbon sequestration and storage benefits the world by eliminating the dangerous greenhouse gas carbon dioxide from the atmosphere (Widyastuti et al. 2018). However, rampant anthropogenic and natural disturbances have caused the degradation of our mangrove forests. These disturbances have caused stored carbon to be released back, causing the accumulation of greenhouse gases in the atmosphere. This study was conducted in the mangrove stand of Santo Niño, Bontoc, Southern Leyte, with the purpose of assessing the species composition and diversity and estimating the biomass and carbon sink potential of the said stand. A total of fifteen, 10x10m were assessed for species present, species count, and number of seedlings, saplings, and trees. A total of twelve mangrove species belonging to four mangrove families were present in the sampled plots, with a species diversity index of 1.727. Regarding the importance value index (IVI), the most important and dominant species belong to the family Avicenniaceae. The sum of all biomasses in the site is 929.70 plus/minus 244.53 t/ha, corresponding to a carbon stock/pool estimate of 464.35 plus/minus 122.27 t C/ha. The species with the highest contribution to the site's biomass and carbon sequestration potential is Sonneratia alba. The results of this study imply that the site is growing and has great potential for carbon sequestration.
Undergraduate thesis (B.S. in Biology) -- University of the Philippines, Tacloban.